Pendekatan Montessori dalam Kemandirian Anak Usia 3-4 Tahun di Satuan PAUD Sejenis Rambutan 33 Kabupaten Jember - Irva rasyidatul Aulia (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study explores the Montessori approach in fostering independence among children aged 3–4 at SPS Rambutan 33 Jember. The aim of this research is to identify and describe how the Montessori approach supports independence in children within this age group. Using qualitative data collection methods, information was obtained through direct classroom observations, in-depth interviews with teachers and parents, as well as documentation of children’s daily activities. The data were then analyzed descriptively to provide an authentic picture of the learning environment and the interactions that take place within it. The findings indicate that the five main areas of the Montessori approach practical life, sensorial, language, mathematics, and culture are consistently applied in daily classroom routines. Practical life activities, such as eating independently, pouring water, and tidying up toys, help children develop a sense of responsibility and basic self-care skills. Sensorial and language activities strengthen concentration, self-confidence, and communication skills, while cultural and mathematical activities foster curiosity, logical thinking, and problem-solving abilities from an early age. Teachers act as facilitators, offering gentle guidance while allowing children the freedom to choose and explore learning materials independently. This environment encourages children to feel comfortable, safe, and motivated to actively participate in every learning activity. Overall, the consistent implementation of the Montessori approach on a daily basis has proven effective in promoting independence among children aged 3–4. These findings provide practical guidance for educators and parents who seek to nurture children’s confidence, decision-making skills, and self-reliance, both at school and at home.
Reupload File Repository_Yudi Approved by Teddy
Keywords: Montessori; Independence; Early Childhood